Proposal for Low-Layer Metadata Collection Technology to Enhance IoT Metadata Utilization - Ryota Shiina; Shinya Tamaki; Che Huang; Tomoya Hatano; Takashi Yamada; Tatsuya Shimada; Tomohiro Taniguchi (IEEE Access)
With the rapid spread of Internet of Things (IoT) services, the number of sensor devices has exploded, and the complexity of managing sensor devices has become a problem. To solve this problem, a metadata-based approach that uses the unique environmental information associated with each device for its management is being developed. This paper focuses on metadata collection for device management and control, and proposes a new collection method that uses low-layer communication while not modifying the existing protocol. Our proposal utilizes the extended area of the probe request (PRQ) frame of IEEE 802.11, which is a layer-2 protocol, to collect metadata. This makes it possible to achieve stable operation even on inexpensive and resource-limited IoT devices, and to realize metadata collection with low communication overhead and power consumption. It is shown to reduce the load on the central processing unit (CPU) and reduce power consumption compared to Internet Protocol (IP) -based metadata collection (layer-3 protocol and above). In addition, in terms of time sensitivity, the collection delay at the time of rising from deep sleep is reduced by 89.8% compared to IP-based techniques. Furthermore, as a benefit of low-layer collection, it enables periodic metadata collection in the background regardless of network connection above the IP layer. To demonstrate this benefit, an example of applying metadata collection to device management is prototyped and its feasibility is experimentally confirmed.